The phenomenality of things: music research in the internet era - Chow, Ow Wei (Universidade de Brasília, 2018)
A modern civilization characterized at the dawn of the Internet of Things has extensively transformed human lifestyle that gives drastic magnitude to virtual connections we make with the surrounding through computer-mediated devices. This new living experience potentially changes the patterns of seeing and thinking. Henceforth, ways of understanding music in the Internet era is no longer linear and singular, while the conventional ethnographic habits of thought and work are to be re-examined. As the rising of both the Internet and the virtuality thinking re-configures the conception of time and spatial dimensions, the existing knowledge of music deemed as ‘real’ and ‘authentic’ may become inadequate today, since all other attributes that shift across time and spaces may have been disregarded from being a part of the reality. A recent doctoral research in Buddhist music, which employs a methodology in virtual ethnography, embarks on a perspective of parallel ideas in phenomenality and virtuality that is tailored to the rising of the Internet. It is often predicted that both the ethnographic methodology positioned in this study and the problematic appearances of music would become issues to ethnographers. However, one of the findings of this study demonstrates that these typical issues could be resolved by the consideration of the following: the virtual property of music is deemed integral to the reality; and the causation of phenomenality in the making of the ethnographic object is significantly regarded. Though the nature of the music acquires an extensive understanding in the Buddhist philosophy, this study proposes a possible approach in the sense-making of contemporary researches in music as a way of knowing.